Developing a listening English learning model using text2speech application - Majid Wajdi; I Nyoman Suka Sanjaya; I Made Sumartana (Journal of Applied Studies in Language, 2021)
The research on the development of "Listening" practice using Text2Speech Applications aims to develop teaching of English, ‘Listening’ for teachers and students who are not experts in the field of information technology. This study tries to discuss how to adopt and adapt Text-to-Speech software / applications in teaching and learning of English. Text2Speech is a computer application (software) that makes it possible to convert written text into spoken text so that it can be heard. By using the Text2Speech application, written text in MS Word format can be converted into spoken text. Text2Speech allows any text to be read in a computer-synthesized voice. By utilizing Text2Speech, written text can be read and sounded so that it can be heard by the user. Text2Speech allows users to determine how to pronounce a word, phrase, sentence, and even text or parts of text. By utilizing the Text2Speech application, teachers and students get "listening" learning materials in native speakers' voices, so that students get used to hearing "listening" teaching materials from native speakers.